2013
DOI: 10.1111/imj.12255
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of point‐of‐care measurement of international normalised ratio using the CoaguChek XS Plus system in the setting of acute ischaemic stroke

Abstract: Point-of-care INR testing correlates well with laboratory values. The results in this study mostly relate to values in the normal range. We suggest that it can be used to try to shorten door-to-needle time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…In other settings like war casualties the time gained using this assay was approximately 26 min compared to the laboratory [11]. In ischemic strokes, time to lysis and detection of oral anticoagulants was reduced [12], and in patients after cardiopulmonary bypass PT was determined much earlier than by the laboratory by using this type of POC device [13].…”
Section: Discussionmentioning
confidence: 99%
“…In other settings like war casualties the time gained using this assay was approximately 26 min compared to the laboratory [11]. In ischemic strokes, time to lysis and detection of oral anticoagulants was reduced [12], and in patients after cardiopulmonary bypass PT was determined much earlier than by the laboratory by using this type of POC device [13].…”
Section: Discussionmentioning
confidence: 99%
“…The normal range of the Quick's value is 70 to 100%, but might depend on the reagents used in different devices. The reliability of these POC devices was investigated in several studies, demonstrating a high correlation of POC results compared with the results of conventional assessment of INR [45][46][47][48][49] and aPTT. 49 No technical difficulties in rapid assessment of INR were observed and all results were normally achieved within 2 minutes.…”
Section: Pt and Aptt: Coaguchekmentioning
confidence: 99%
“…46,48 Nusa and colleagues thus concluded that POC INR measurements should be used to shorten door-to-needle time in patients after an acute ischemic stroke. 45 To support on-site decision making, POC INR devices provide fast and reliable results for patients with suspected deficiencies of coagulation factors and are also feasible in prehospital emergency care. 47,49 Nonetheless, the CoaguChek is approved only to monitor the effect of vitamin K antagonists (e.g., phenprocoumon).…”
Section: Pt and Aptt: Coaguchekmentioning
confidence: 99%
“…The paper by Nusa et al . investigates the use of a blood clotting point of care device (CoaguChek XS System; Roche Diagnostics, Mannheim, Germany) to derive quickly international normalised ratio (INR) prior to commencing stroke thrombolysis.…”
mentioning
confidence: 99%
“…[8][9][10] These approaches are best implemented across healthcare services, and indeed, many Australian ambulance services have updated clinical protocols to enable a system-wide approach, with excellent results. 9,11 The paper by Nusa et al 12 investigates the use of a blood clotting point of care device (CoaguChek XS System; Roche Diagnostics, Mannheim, Germany) to derive quickly international normalised ratio (INR) prior to commencing stroke thrombolysis. Standard laboratory INR testing can take up to 30 min (or longer), which is unacceptable in the context of the time-critical treatment of acute ischaemic stroke.…”
mentioning
confidence: 99%